Cavitands as Reaction Vessels and Blocking Groups for Selective Reactions in Water. (2nd June 2016) - Masseroni, Daniele; Mosca, Simone; Mower, Matthew P.; Blackmond, Donna G.; Rebek, Julius
Abstract: The majority of reactions currently performed in the chemical industry take place in organic solvents, compounds that are generally derived from petrochemicals. To promote chemical processes in water, we examined the use of synthetic, deep water‐soluble cavitands in the Staudinger reduction of long‐chain aliphatic diazides (C8, C10, and C12 ). The diazide substrates are taken up by the cavitand in D2 O in folded, dynamic conformations. The reduction of one azide group to an amine gives a complex in which the substrate is fixed in an unsymmetrical conformation, with the amine terminal exposed and the azide terminal deep and inaccessible within the cavitand. Accordingly, the reduction of the second azide group is inhibited, even with excess phosphine, and good yields of the monofunctionalized products are obtained. In contrast, the reduction of the free diazides in bulk solution yields diamine products.